Non-supply of electricity in resource constrained electricity systems. (1st January 2002) - Balachandra, P.; Chandru, Vijay
Shortages in the supply of electricity in resource constrained electricity systems of developing nations is a poorly documented but commonly observed phenomena. The literature on electricity systems has a perspective on the issue of interruptions in the supply of electricity that focuses on the high cost of unpredictable but infrequent interruptions. This "reliability" perspective does not seem appropriate in the study of chronically constrained power systems. This paper presents a look at the issue of non-supply of electricity its causes, its consequences and its implications for policy in resource constrained systems.